2019
DOI: 10.1097/aog.0000000000003228
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Rupture at Term in a Patient With Abdominal Cerclage

Abstract: BACKGROUND: When labor ensues in the setting of transabdominal cerclage, uterine rupture is a potential complication associated with significant morbidity and mortality for both mother and fetus. CASE: A woman with a transabdominal cerclage presented at 39 2/7 weeks of gestation with contractions, tachycardia, abdominal pain, and fetal bradycardia. Emergent cesarean delivery revealed a ruptured uterus with fetus and placenta floating in the abdomen. Neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…For patients with an in situ transabdominal cerclage, cesarean delivery is recommended between 37 0/7 and 39 0/7 gestational weeks. [ 15 ] Dandapani et al [ 16 ] reported the experience of a woman with a transabdominal cerclage who was admitted at 39 2/7 gestational weeks, presenting with contractions, abdominal pain, and fetal bradycardia. Emergency cesarean delivery revealed a ruptured uterus with the fetus and placenta floating in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with an in situ transabdominal cerclage, cesarean delivery is recommended between 37 0/7 and 39 0/7 gestational weeks. [ 15 ] Dandapani et al [ 16 ] reported the experience of a woman with a transabdominal cerclage who was admitted at 39 2/7 gestational weeks, presenting with contractions, abdominal pain, and fetal bradycardia. Emergency cesarean delivery revealed a ruptured uterus with the fetus and placenta floating in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The primary high-risk factors for uterine rupture at non-cesarean scar sites predominantly involve concealed scar uterus (involving a history of induced abortion and hysteroscopy surgery), fetal malposition, inadequate development of the uterine muscle layer, anomalous uterine development, external version procedures, multiparity, placental abnormalities, labor induction using drugs, fetal head disproportion, uterine adenomyosis, connective tissue disorders, a history of ectopic pregnancy, and laparoscopic cervical cerclage. [1,[4][5][6] Hysteroscopic surgery is increasingly common and serves an indispensable role in diagnosing and managing intrauterine diseases. Uterine rupture during pregnancy subsequent to hysteroscopic surgery constitutes a long-term complication of these procedures.…”
Section: Etiologymentioning
confidence: 99%
“…Other complications, including uterine perforation, pelvic infection, bowel injury, or bladder injury, are overall rare (1.1% of laparoscopic cerclages) (5). Single case reports have documented suture migration through the cervix, erosion into the vagina, or uterine rupture with an abdominal cerclage in place (34,35).…”
Section: Laparoscopic Approachmentioning
confidence: 99%